Optimization of T-shaped magnetic separator filtering abilities - Aksyonov, D.S. (Вопросы атомной науки и техники, 2012)
Computer simulation was used to study influence of design parameters of T-shaped magnetic filter (separator) baffles on degree of plasma cleaning from macroparticles. Baffle system design for such filter was developed. Evaluation and development of highly effective conceptual baffle system was performed. Recommendations for designing of baffle systems of macroparticle filters were made. При помощи компьютерного моделирования исследовано влияние конструктивных параметров рёбер T-образного магнитного фильтра (сепаратора) на степень очистки плазмы от макрочастиц. Разработана конструкция рёберной системы для такого фильтра. Произведена оценка и разработка высокоэффективной концептуальной рёберной системы. Выработаны рекомендации касательно проектирования рёберных систем фильтров. За допомогою комп'ютерного моделювання досліджено вплив конструктивних параметрів ребер T-подібного магнітного фільтра (сепаратора) на ступінь очищення плазми від макрочастинок. Розроблено конструкцію реберної системи для такого фільтра. Проведені оцінка та розробка високоефективної концептуальної системи ребер. Разроблені рекомендації щодо проектування реберних систем фільтрів.